Structural Characterization of the Intrinsically Disordered Protein p53 Using Raman Spectroscopy. Issue 5 (May 2017) - Signorelli, Sara; Cannistraro, Salvatore; Bizzarri, Anna Rita
The intrinsically disordered protein p53 has attracted a strong interest for its important role in genome safeguarding and potential therapeutic applications. However, its disordered character makes difficult a full characterization of p53 structural architecture. A deep knowledge of p53 structural motifs could significantly help the understanding of its functional properties, in connection with its complex binding network. We have applied Raman spectroscopy to investigate the structural composition and the conformational heterogeneity of both full-length p53 and its DNA binding domain (DBD), in different solvent environments. In particular, a careful analysis of the Amide I Raman band, which is highly sensitive to protein secondary structure elements such as α-helices, β-sheets and random coils, has revealed the presence of extended random coils in p53 and predominant β-sheet regions in its DBD. In addition, this analysis has allowed us to explore the ensemble of interchanging conformations in both p53 and its DBD, highlighting a higher conformational heterogeneity in p53 than in its DBD. Furthermore, by applying a principal components analysis, we have identified the principal spectral markers in both p53 and DBD samples. The combination of the two approaches could be insightful for the study of intrinsically disordered proteins, by offering increased versatility and wide application as a label-free, real-time and non-invasive detection method.